Pengaruh Model Problem Based Learning terhadap Kemampuan Metakognitif Siswa Kelas IV Pada Mata Pelajaran PAI Materi Kisah Hijrah Nabi Muhammad SAW Ke Madinah di SD IT ZU TSAQIF Desa Kolam Kec. Percut Sei Tuan Kab. Deli Serdang - Ulfa, Siti Maryam; Sinaga, Ali Imran; Nasution, Zulkipli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study entitled The Effect of Problem Based Learning Model on Metacognition of Fourth Grade Students in Islamic Religious Education Subject with the Material of the Story of the Prophet Muhammad's Hijrah to Medina at SD IT Zu Tsaqif, Kolam Village, Percut Sei Tuan District, Deli Serdang Regency aims to analyze the effect of the application of the Problem Based Learning (PBL) learning model on the metacognition abilities of fourth grade students in Islamic Religious Education subject with the Material of the Story of the Prophet Muhammad's Hijrah to Medina at SD IT Zu Tsaqif. This study was conducted using a total sampling technique, namely using the entire population as a research sample. Documentation, questionnaires, and observations are examples of data collection tools. Based on the results of the correlation test, a significance value (2-tailed) of 0.000 was obtained, which means it is less than 0.05. This shows that the metacognitive skills of the experimental class and the control class before and after the application of the learning model on the material of the Prophet Muhammad's Hijrah to Medina were significantly different.